VITAMIN B12 AND FOLIC ACID DEFICIENCY IN GIRLS OF EARLY REPRODUCTIVE AGE IN KHOREZM REGION - Sultanmuratova, G.U.; Matyakubova, S.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Vitamin B12 and folic acid deficiency is a pressing medical and social problem, especially among girls of early reproductive age. These substances play a key role in hematopoiesis, cell division and nervous system functioning. The aim of this study was to investigate the frequency of vitamin B12 and folic acid deficiency in girls with anemia in Khorezm region. The study included 97 girls of early reproductive age, in whom the level of vitamin B12 and folic acid in the blood serum was determined using the ELISA method. Vitamin B12 deficiency was detected in 7.2% of the examined patients, and folic acid deficiency in 24.7%. The obtained results indicate the presence of micronutrient deficiency in this population and emphasize the need for early diagnosis and correction of these deficiency conditions.